The Implementation of AI-Based Information Retrieval System at the University of North Sumatera Library - Halbert Alfonsus Sihaloho; Fransiska Timoria Samosir; Rahmat Alifin Valentino (Program Studi Ilmu Perpustakaan UIN Alauddin, 2025)
This study examines the implementation of an artificial intelligence (AI)–based information retrieval system at the University of North Sumatra (USU) Library. The research aims to describe how the system has been applied, particularly in supporting electronic journal searches. A descriptive qualitative approach was used, with data collected through observations, interviews, and document analysis. Six informants participated in the study, including the head librarian, librarians, lecturers, and students. The findings show that the AI chatbot is capable of interpreting user search intent through Natural Language Processing (NLP), processing queries intelligently, and providing fast, relevant, and detailed results from 18 electronic journal databases subscribed to by the USU Library. Users reported substantial time savings and greater convenience in obtaining accurate academic references. Overall, the introduction of AI has contributed positively to the quality of information services, although challenges remain in areas such as infrastructure, staff training, and digital collection development. The study concludes that AI-based information retrieval represents a strategic innovation for enhancing library services, enabling them to become more adaptive, efficient, and responsive in the digital era.